Discovery of isonucleotidic CDNs as potent STING agonists with immunomodulatory potential - Dejmek, Milan; Šála, Michal; Brazdova, Andrea; Vanekova, Lenka; Smola, Miroslav; Klíma, Martin; Břehová, Petra; Buděšínský, Miloš; Dračínský, Martin; Procházková, Eliška; Zavřel, Martin; Šimák, Ondřej; et al. (Structure (London, England, 2022)
Stimulator of interferon genes (STING) is an adaptor protein of the cGAS-STING signaling pathway involved in the sensing of cytosolic DNA. It functions as a receptor for cyclic dinucleotides (CDNs) and, upon their binding, mediates cytokine expression and host immunity. Besides naturally occurring CDNs, various synthetic CDNs, such as ADU-S100, have been reported to effectively activate STING and are being evaluated in clinical trials for the treatment of cancer. Here, we describe the preparation of a unique new class of STING agonists: isonucleotidic cyclic dinucleotides and the synthesis of their prodrugs. The presented CDNs stimulate STING with comparable efficiency to ADU-S100, whereas their prodrugs demonstrate activity up to four orders of magnitude better due to the improved cellular uptake. The compounds are very potent inducers of inflammatory cytokines by peripheral blood mononuclear cells (PBMCs). We also report the X-ray crystal structure of the lead inhibitor bound to the wild-type (WT) STING.
Keywords: cytokines; nukleotidy cyklické; Leukocytes, Mononuclear; prodrugs; leukocyty mononukleární; membránové proteiny; Membrane Proteins; cancer; isonucleosides; Nucleotides, Cyclic; cyclic dinucleotides; cytosol; Prodrugs; prekurzory léčiv; STING agonists; Cytosol